Strength and permeability of stabilized peat soil - Wong, L.S.; Hashim, Roslan; Ali, F.H. (2008)
The aim of this study was to analyze the unconfined compressive strength and initial permeability of peat soil stabilized by a mixture of Ordinary Portland cement, ground granulated blast furnace slag and siliceous sand. An understanding of the stabilized soil properties is of great importance for the design of deep stabilization in peat land for highway construction. Significant evidence on the positive effects of the admixture at stabilizing peat soil was discovered from laboratory testing investigation of the study. Results from the investigation indicated that addition of the admixture was able to increase unconfined compressive strength and reduce initial permeability of the stabilized soil as compared to those of untreated peat.